Tumor Microenvironment Stimuli‐Responsive Fluorescence Imaging and Synergistic Cancer Therapy by Carbon‐Dot–Cu2+ Nanoassemblies. (11th September 2020) - Sun, Shan; Chen, Qiao; Tang, Zhongdi; Liu, Chuang; Li, Zhongjun; Wu, Aiguo; Lin, Hengwei
Abstract: A method is developed to fabricate tumor microenvironment (TME) stimuli‐responsive nanoplatform for fluorescence (FL) imaging and synergistic cancer therapy via assembling photosensitizer (chlorine e6, Ce6) modified carbon dots (CDs‐Ce6) and Cu 2+ . The as‐obtained nanoassemblies (named Cu/CC nanoparticles, NPs) exhibit quenched FL and photosensitization due to the aggregation of CDs‐Ce6. Their FL imaging and photodynamic therapy (PDT) functions are recovered efficiently once they entering tumor sites by the stimulation of TME. Introducing of Cu 2+ not only provides extra chemodynamic therapy (CDT) function through reaction with hydrogen peroxide (H2 O2 ), but also depletes GSH in tumors by a redox reaction, thus amplifying the intracellular oxidative stress and enhancing the efficacy of reactive oxygen species (ROS) based therapy. Cu/CC NPs can act as a FL imaging guided trimodal synergistic cancer treatment agent by photothermal therapy (PTT), PDT, and thermally amplified CDT. Abstract : A tumor microenvironment (TME) stimuli‐responsive fluorescence imaging and trimodal synergistic cancer treatment nanoplatform is facilely constructed via assembling carbon dots and Cu 2+ . This could act as a potential strategy to achieve enhanced cancer therapeutic efficiency with minimized side effects.